Content Analysis of the #AllEyesOnPapua Movement Messages on Instagram Social Media) - Kharis Khamdani (Prospect Publishing, 2024)
This research describes the content of messages in the #AllEyesOnPapua movement on Instagram social media. #AllEyesOnPapua is an environmental campaign that helps the Awyu and Moi tribes to seize their traditional forests which will be used as oil palm plantations by PT Indo Asiana Lestari. This research uses a qualitative method with a message content analysis approach. This research aims to analyze what kind of messages are conveyed through the #AllEyesOnPapua movement. In posts that include #AllEyesOnPapua, there are several styles of messages conveyed, such as education and invitation, the use of Instagram features also helps in conveying this movement. The conclusion of this research is that the messages from the #AllEyesOnPapua movement are able to attract public attention.